The Limitation of Liability of the Marine Carrier of Goods in Omani Law: Comparative Study - Qassaymeh, Maen (Mohammad Ali) S Al; Al Barashdi, Saleh Hamed Mohammed (Journal of Ecohumanism, 2025)
This research discusses the limitation of the liability of the carrier of the goods who carries the goods via the sea; it focuses on the limitation in case of destruction and in case of damage of the goods. This is because the carrier is considered liable if the goods destructed or damaged during the voyage while they are under his possession and, precisely, when the destruction or the damage comes from his mistake. The rules of limitation are regulated in order to keep the carrier away from financial exhaustion. This critical position may come as a result of the large amount of goods which the vessel may carry and some of these goods may have large value. Therefore, the laws usually set rules protect the carrier from an unlimited liability. These rules determine a maximum limit for the liability of the carrier to ensure that this liability remains within reasonable level even if the destructed or the damaged goods have large value. This study comes to discuss the limitation of liability of the carrier in Omani Law. It aims at comparing this limitation with the international criteria that are regulated in the international conventions, particularly, Hamburg Convention and Rotterdam Convention.